2021
DOI: 10.3389/fonc.2021.728464
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Colon Cancer Effects of Essential Oil of Curcuma phaeocaulis Through Tumour Vessel Normalisation

Abstract: BackgroundNormalising tumour vessels had become a significant research focus in tumour treatment research in recent years. Curcumae rhizoma (CR) is an essential plant in traditional Chinese medicine as it promotes blood circulation and removes blood stasis. Similarly, CR improves local blood circulation.PurposeWe explored the anti-colon cancer effects of essential oil from CR (OCR) by investigating its role in normalising tumour vessels. We also provided a basis for research and development into new anti-cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Jain et al [11] reported that angiogenesis inhibitors could moderately inhibit angiogenesis, "normalize" tumor blood vessels and restore the structure and function of blood vessels. In addition, it can provide suitable treatment time and dose reference for other cytotoxic treatments [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Jain et al [11] reported that angiogenesis inhibitors could moderately inhibit angiogenesis, "normalize" tumor blood vessels and restore the structure and function of blood vessels. In addition, it can provide suitable treatment time and dose reference for other cytotoxic treatments [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…EOs from Croton flavens leaf were observed to be effective on human lung carcinoma and human colon adenocarcinoma cell lines, respectively [ 46 ]. Another study identified that an EO from Curcumae rhizoma (CR) inhibited the growth of colon cancer by improving tumor vessel structure, reducing angiogenesis in tumors, and normalizing tumor vessels in both in vitro and in vivo models [ 47 ]. Similarly, a recent study demonstrated that oregano EO-based nanoemulsion increased prostate cancer cell death through apoptosis and decreased lipid droplet accumulation via targeting HMGCR, FASN, and SREPB1 signals in vitro [ 48 ].…”
Section: Therapeutic Effects Of Eosmentioning
confidence: 99%
“…The molecular mechanism was defined in in vitro experiments, where culture of mice aortic-segments treated with atorvastatin demonstrated inhibited Ang2 release and higher expression of VE-Cadherin, accompanied by decreased VE-Cadherin (Y685) phosphorylation in ECs, which resulted in increased pericyte coverage [ 103 ]. VE-Cadherin is crucial for proper vascular development, its close association with pericyte coverage and angiogenesis was demonstrated also in tumours [ 104 ] and retinal vasculature development [ 105 ].…”
Section: As Treatments With Pericyte-mediated Effectsmentioning
confidence: 99%